Pizza czar - Falco, Anthony (Abrams, 2021)
"In his comprehensive first book, legendary pizza czar Anthony Falco teaches you everything you need to know to make pizza wherever you are, drawing from his singular experience opening pizzerias around the globe. If there's one thing the entire world can agree on, it's pizza. It just might be the world's favorite food. In every climate, in every region, in every kind of kitchen, there's pizza to be had, infused with local flavor. In this definitive book, filled with hacks, tips, and secret techniques never before shared, International Pizza Consultant Anthony Falco brings the world of pizza to your kitchen, wherever you are. After eight years at the famous Brooklyn restaurant Roberta's, culminating with his position as Pizza Czar, Falco pivoted from the New York City food scene to the world, traveling to Brazil, Colombia, Kuwait, Panama, Canada, Japan, India, Thailand, and all across the United States. His mission? To discover the secrets and spread the gospel of making the world's favorite food better. Now the planet's leading expert pizza consultant, he can make great pizza 8,000 feet above sea level in Bogotá or in subtropical India, and he can certainly help you do it at home. An exhaustive resource for absolutely any pizza cook, teaching mastery of the classics and tricks of the trade as well as completely unique takes on styles and recipes from around the globe, Pizza Czar is here to help you make world-class pizza from anywhere on the map."--Publisher's website.